2017
DOI: 10.24275/uam/izt/dcbs/hidro/2017v27n2/cantoral
|View full text |Cite
|
Sign up to set email alerts
|

Cyanotoxins: environmental and health effects. Prevention measures

Abstract: RESUMENAntecedentes. Ante los eventos de florecimientos de cianobacterias cada vez más frecuentes a nivel global, cuyos efectos son tóxicos y negativos para la salud humana, las mascotas, los animales del campo, la vida acuática y silvestre, es indispensable hacer pública la información más relevante respecto a este tema, ya que estos eventos tendrán cada vez más una mayor incidencia y frecuencia en un contexto de calentamiento global. Objetivos. Entre los objetivos principales de esta investigación destacan e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…When studies reported several species Distribution, water bodies and cyanotoxin types. Despite the global distribution of cyanobacteria and cyanotoxins (Mowe et al, 2015, Flores et al, 2018, Svirčev et al, 2019 and the known potential risk for species that are exposed to cyanotoxins, including humans (Codd et al, 2005, Burrati et al, 2017, Cantoral Uriza et al, 2017, Pham & Utsumi 2018, Banerjee et al, 2021, cyanotoxins accumulation in freshwater organisms in Latin America has been evaluated only in four countries. Brazil is the country having more field studies of cyanotoxins bioaccumulation (13 studies), followed by México (4), Argentina (3) and, finally, Uruguay with only one study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When studies reported several species Distribution, water bodies and cyanotoxin types. Despite the global distribution of cyanobacteria and cyanotoxins (Mowe et al, 2015, Flores et al, 2018, Svirčev et al, 2019 and the known potential risk for species that are exposed to cyanotoxins, including humans (Codd et al, 2005, Burrati et al, 2017, Cantoral Uriza et al, 2017, Pham & Utsumi 2018, Banerjee et al, 2021, cyanotoxins accumulation in freshwater organisms in Latin America has been evaluated only in four countries. Brazil is the country having more field studies of cyanotoxins bioaccumulation (13 studies), followed by México (4), Argentina (3) and, finally, Uruguay with only one study.…”
Section: Methodsmentioning
confidence: 99%
“…To what extent the aquaculture constitutes an important route of transfer of cyanotoxins to humans is still unknown, and it should be determined in future studies. Also, as noted by Cantoral Uriza et al, (2017), it is important to investigate unknown cyanobacteria species from tropical areas in Latin America to access their potential toxicity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation